Design and seismic response of tall chevron panel buckling‐restrained braced steel frames. (19th December 2011) - Ding, Yukun; Zhang, Yaochun
SUMMARY: The numerical analysis of the seismic performance for tall chevron panel buckling‐restrained braced steel frames (PBRBFs) under small and strong earthquake excitations has been carried out to investigate a capacity design procedure for chevron PBRBFs and to examine the effects of axial strength distribution of braces along the height of buildings, vertical supports of braces for the braced beams and the overstrength of braces on the seismic response of PBRBFs. It revealed that the chevron braces that remained elastic can actually provide the vertical supports for the braced beams. Under severe earthquake excitations, the vertical supports deteriorated greatly after braces yielding. The PBRBFs designed by omitting vertical supports of braces for the braced beams and considering the overstrength of braces exhibited superior performance with smaller plastic deformations for braced beams and reduction in ductility demands for panel buckling‐restrained braces (PBRBs) as compared with the others. The distribution of yielding for PBRBs in 10‐story buildings verified that the participation from the higher modes is not very remarkable and that the capacity design based on the first‐mode response can be considered for multistory PBRBFs. Moreover, on the basis of the analysis results of the 30‐story PBRBF, the participation of the higher modes should be taken into account for high‐rise PBRBFs. Copyright © 2011 John Wiley & Sons, Ltd.